An annotated catalog of the Iranian Pyrrhocoridae (Hemiptera: Heteroptera: Pentatomomorpha: Pyrrhocoroidea) - Ghahari, Hassan; Moulet, Pierre (Zootaxa, 2013)
The species diversity of Pyrrhocoridae is cataloged in this paper. Seven species (from three genera: Aderrhis Bergroth 1906, Pyrrhocoris Fallén 1814, Scantius Stål 1866) are given as the fauna of Iran.